Plasma Dickkopf-1 Levels Are Associated with Chronic Kidney Disease - Yu-Hsuan Li; Yu-Cheng Cheng; Junyi Wu; I-Te Lee (Metabolites)
Background: Wnt/β-catenin signaling is important in the development and repair of the kidney. Dickkopf-1 (DKK-1) is characterized as an inhibitor of the Wnt/β-catenin signaling pathway. Purpose: We examined the relationship between plasma DKK-1 levels and the risk of chronic kidney disease (CKD). Methods: In this cross-sectional study, patients without known diabetes mellitus who were admitted for coronary angiography due to angina were enrolled. Fasting blood samples were collected at a predetermined outpatient visit. Results: Among 373 enrolled patients, 62 (16.6%) were in the CKD group, and 311 (83.4%) were in the nonCKD group. Plasma DKK-1 levels were significantly higher in the CKD group than in the nonCKD group (697.2 ± 174.7 vs. 589.0 ± 193.3 pg/mL; p < 0.001). Plasma DKK-1 levels were inversely correlated with the eGFR (Pearson’s correlation coefficient = −0.265; p < 0.001). On the basis of multivariable logistic regression analyses, patients in the highest DKK-1 quartile had a significantly greater risk of CKD (OR = 4.188; 95% CI: 1.564, 11.212; p = 0.004) than did those in the lowest DKK-1 quartile. Conclusions: Plasma DKK-1 levels are associated with the risk of CKD in patients with angina. Further studies investigating the underlying mechanisms involved in the relationship between DKK-1 and CKD are warranted.